Blueprint of Ride Haven Enterprise / Nurul Atikah Muda - Muda, Nurul Atikah (2020)
Our main product is OurFamilyBike. OurFamilyBike is a combination of bike and stroller in one complete unit. The innovation of this product is it can be detachable and convertible. In detail, this bike stroller can be transformed to be one single unit of stroller that is portable within a minute. This transformation has allowed the bike stroller to be brought inside a building, shopping mall, elevator or even in a public transportation. The aim of this product is to ease and give freedom to parents, guardians, and babysitters to go anywhere while watching their kids at the same time. Also, this product gives chances for parents to get in shape and burn calories by cycling. Furthermore, it gives convenience to parents who live in apartments or flats to keep the bike stroller in their car. Therefore, our main target market are parents, babysitters, and guardians between 18 years old to 55 years old who have small children that need to be taken care of